2021
DOI: 10.3389/fcell.2021.636295
|View full text |Cite
|
Sign up to set email alerts
|

Quality Matters? The Involvement of Mitochondrial Quality Control in Cardiovascular Disease

Abstract: Cardiovascular diseases are one of the leading causes of death and global health problems worldwide. Multiple factors are known to affect the cardiovascular system from lifestyles, genes, underlying comorbidities, and age. Requiring high workload, metabolism of the heart is largely dependent on continuous power supply via mitochondria through effective oxidative respiration. Mitochondria not only serve as cellular power plants, but are also involved in many critical cellular processes, including the generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 272 publications
0
27
0
Order By: Relevance
“…To prevent and reduce mitochondrial dysfunction, the cell activates coordinated processes that constitute mitochondrial quality control: mitochondrial dynamics, biogenesis and mitophagy [ 6 , 7 ]. Mitochondrial biogenesis is the process of synthesis of new mitochondria, which is triggered by the transcription factor PPAR-gamma co-activator 1 alpha (PGC1α) after AMP-activated kinase (AMPK) activation.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent and reduce mitochondrial dysfunction, the cell activates coordinated processes that constitute mitochondrial quality control: mitochondrial dynamics, biogenesis and mitophagy [ 6 , 7 ]. Mitochondrial biogenesis is the process of synthesis of new mitochondria, which is triggered by the transcription factor PPAR-gamma co-activator 1 alpha (PGC1α) after AMP-activated kinase (AMPK) activation.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage between β-cell dysfunction and neurodegeneration during the aging process has been shown by studies with the purpose to clarify the interrelationship between glycometabolic derangement, mitochondrial dysfunction related oxidative stress, inflammatory response, and PD via investigating dietary effect on PD risk [87][88][89]. In agreement with this, the ketogenic diet containing very low carbohydrates was reported to be anti-inflammatory and neuroprotective against mitochondrial complex I inhibitors in both MPTP and 6-OHDA neurotoxic PD animal models [90,91]. Another study also suggested a dietary pattern consisting of high intakes of vegetables, fruits, and fish is associated with a decreased risk of PD in Japanese by measuring overall cumulative dietary pattern [92].…”
Section: The Linkage Between Dm and Pdmentioning
confidence: 71%
“…Typically, a blood clot or plaque forms in an artery supplying the brain, thereby causing a blockage of blood flow to the brain. Blood restriction causes a decrease in oxygen and glucose to tissues, leading to mitochondrial dysfunction [ 93 , 94 ]. Increased mitochondrial dysfunction results in decreased oxidative metabolism and ATP, coupled with an increase in toxic reactive oxygen and nitrogen species (ROS and RNS).…”
Section: Secondary Neurodegenerative Disordersmentioning
confidence: 99%